Michael Simpson - paintings and drawings 1989-2019 - Burnett, Craig; Fletcher, Jess (Blain/Southern, 2019)
Michael Simpson (b.1940 Dorset, England) is an artist whose work is characterised by a reduced palette and a distinctive vocabulary of "Benches", "Confessionals" and "Squints", three motifs that appear in three separate series of paintings within his oeuvre. Whilst his apparent subject is the infamy of religious history and the politics of belief, these subjective references provide only a subtext for his principal subject - the mechanics of painting. A "leper squint" is a feature built into the walls of medieval churches which allowed sufferers of leprosy and other "undesirables" to view sermons while remaining outside. In Simpson's paintings the squint appears as a rectangular aperture placed high up on outer walls with various architectural means to reach it. They invite the viewer to approach yet their structure frustrates the desire to see what might lie beyond. In 2016, Michael Simpson won the John Moores Painting Prize for his painting, Squint (19). This catalogue features the artist's recent work from the ongoing Squint series, alongside a selection of his other paintings and drawings from the past 30 years. Exhibition: Blain/Southern, London, UK (02.10.2019 - 25.01.2020)
Impressum: Published on the occasion of the exhibition "Michael Simpson: New Paintings", 2 October-16 November 2019
Keywords: Simpson, Michael -- 1940-; Geschichte 1989-2019; Malerei; Zeichnung; Ausstellungskatalog -- BlainSouthern -- 02.10.2019-16.11.2019 -- London; Bildband